2003
DOI: 10.1063/1.1525067
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistance measurement on single crystal silicon nanowires

Abstract: A p-type single crystal silicon nanowire bridge and a four-terminal nanowire element were fabricated by electron-beam direct writing. The piezoresistance was investigated in order to demonstrate the usefulness of these sensing elements as mechanical sensors. The longitudinal piezoresistance coefficient πl[110] was found to be 38.7×10−11 Pa−1 at a surface impurity concentration of Ns=9×1019 cm−3 for the nanowire bridge. The shear piezoresistance coefficient π44 was found to be 77.4×10−11 Pa−1 at Ns=9×1019 cm−3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
52
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 5 publications
4
52
0
Order By: Relevance
“…In terms of directional considerations, the h100i, h110i, and h111i are the most important directions for the electrical transport properties of strained Si (particular one-dimensional Si) in practical applications or theoretical investigations. Interestingly, the electrical transport properties of strained h111i and h110i oriented one-dimensional Si nanostructures have been studied experimentally, [33][34][35][36][37][38] while very few reported on the understanding of the strained h100i orientated Si through experiments. 39 The current understanding of the electrical transport properties of strained h100i-oriented Si was limited by theoretical considerations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of directional considerations, the h100i, h110i, and h111i are the most important directions for the electrical transport properties of strained Si (particular one-dimensional Si) in practical applications or theoretical investigations. Interestingly, the electrical transport properties of strained h111i and h110i oriented one-dimensional Si nanostructures have been studied experimentally, [33][34][35][36][37][38] while very few reported on the understanding of the strained h100i orientated Si through experiments. 39 The current understanding of the electrical transport properties of strained h100i-oriented Si was limited by theoretical considerations.…”
mentioning
confidence: 99%
“…7,11 For Si, efforts have been paid to alter the carrier transport properties induced by strain in order to find highly sensitive strain gauges or a more effective mode to enhance the carrier mobility by theoretical calculations [21][22][23][24][25][26][27][28][29][30][31] or experiments. [32][33][34][35][36][37][38] It has been well demonstrated that the orientation, size, doping type, and level as well as the strain state are the primary factors 22,26,30,31 affecting the band structure, carrier effective mass, and electric properties for strained crystalline Si. In terms of directional considerations, the h100i, h110i, and h111i are the most important directions for the electrical transport properties of strained Si (particular one-dimensional Si) in practical applications or theoretical investigations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports of giant piezoresistive effects in p-type silicon nanowires ͑SiNWs͒ have appeared recently; gauge factors more than an order of magnitude larger than seen in conventional microscale piezoresistors were reported. [6][7][8] It was convincingly suggested by Rowe 9 that the giant piezoresistive effect in SiNWs originates from a stressinduced modulation of the surface depletion region due to changes in surface state charge and neutral level; hence, the observed large gauge factors may be difficult to apply to stable piezoresistive sensors. Recently, Rowe et al 10 showed that giant gauge factors may be realized in microscale devices.…”
Section: Introductionmentioning
confidence: 99%
“…The atomic behavior of the silicon nanowires is becoming more complex since the size effect, surface effect and quantum effect of the silicon material are particularly significant. 2,3 So far the silicon nanowires are characterized by some experiments, 4 and theoretical studies which are based on continuum theory and some molecular dynamic softwares. But inherent continuum theory model can not accurately explain the vibration behavior of the silicon nanowires, and a huge computational resource is needed when the performance of silicon nanowires is simulated using molecular dynamics softwares.…”
Section: Introductionmentioning
confidence: 99%